Determinasi Resiko Keamanan Pangan Berdasarkan Kandungan Escherichia coli Pada Ikan Budi Daya Mina Padi Banyumas - Syuraihanah, Khotoh; Mulandari, Kusriyah; Sukardi, Purnama; Mardiyana, Mardiyana (MAIYAH, 2024)
Mina padi is a way of raising fish between rice plants, as an interval between the two rice planting seasons or raising fish as a substitute for crops in the rice fields. Panembangan Village is one of the areas in Banyumas Regency which carries out fish farming using the mina padi system with the fish reared in this cultivation being Tilapia Fish (Oreochromis niloticus) where this fish is a superior commodity from Banyumas Regency. The purpose of this study is determine the content of E. coli bacteria and how the food safety conditions in tilapia fish (O. niloticus) from the cultivation of mina padi in Panembangan Village are based on applicable standards. The analytical method used is the MPN (Most Probable Number) method with the SNI 01-2332.1-2006 and SNI 7388:2009. The results of this study found that tilapia (O. niloticus) from mina padi cultivation contained E. coli bacteria ranging from 9.1x101 – 7.3x103 colonies/gr. The content of E. coli bacteria in the cultivation of mina padi in Panembangan Village comes from the water used in the mina padi system and has exceeded the standard (<3 APM/gr) which indicates that tilapia fish (O. niloticus) is unsafe for consumption. So based on the results of this study it is necessary to monitor the water sources used and the management of fishery products so that the fish produced by Mina Padi cultivation are suitable for consumption.